Rapid Improvement of Canine Cognitive Dysfunction with Immunotherapy designed for Alzheimer’s Disease - Bosch, Maria Neus; Bayon, Javier Gimeno-; Rodriguez, Manuel J; Pugliese, Marco; Mahy, Nicole (Current Alzheimer Research, 2013)
Immunotherapy against amyloid-β(Aβ) may improve rodent cognitive function by reducing amyloid neuropathology and is being validated in clinical trials with positive preliminary results. However, for a complete understanding of the direct and long-term immunization responses in the aged patient, and also to avoid significant side effects, several key aspects remain to be clarified. Thus, to investigate brain Aβ clearance and Th2 responses in the elderly, and the reverse inflammatory events not found in the immunized rodent, better Alzheimer's disease (AD) models are required. In the aged familiar canine with a Cognitive Dysfunction Syndrome (CDS) we describe the rapid effectiveness and the full safety profile of a new active vaccine candidate for human AD prevention and treatment. In these aged animals, besidesa weak immune system, the antibody response activated a coordinated central and peripheral Aβ clearance, that rapidly improved their cognitive function in absence of any side effects. Our results also confirm the interest to use familiar dogs to develop innovative and reliable therapies for AD.
Keywords: amyloid vaccine